L’organisation socio-économique des écuries de Chantilly durant la première moitié du XVIIIe siècle - Christophe Levadoux (In Situ)
Commissioned by Louis-Henri de Bourbon-Condé (1692-1740) between 1719 and 1735, and built from plans drawn up by Jean Aubert, the construction of the Great Stables of Chantilly was an important feature in the site development plan and the urbanisation of the village of Chantilly. Their powerful architecture has shaped the surrounding landscape, creating an impressive vision, and their socio-economic structure reflects a certain ideal in the lifestyle of the aristocracy. The variety of horses, the multitude of carriages, the staff members, the customs and traditions surrounding this lifestyle and those who kept them, highlight the originality and importance of this noble occupation, studies of which have in part been made possible thanks to account books preserved at the Musée Condé in Chantilly.